Wind tunnel site analysis of Dow Chemical Facility at Rocky Flats, Colorado, part II - Meroney, R. N., author; Peterka, J. A., author; Hoot, T. G., author; Department of Civil Engineering, Colorado State University, publisher (Colorado State University. Libraries, 1973)
This report deals with two separate problems occurring at the Dow Chemical Company Plutonium Recovery Facility, Rocky Flats Division, namely the dispersion of potential effluents and the protection of parking areas from the destructive action of high velocity west winds by the use of shelterbelts. The dispersion study is a continuation of a previous study and consisted of modeling the geography, wind and turbulence profiles and effluent releases in a wind tunnel study. Dispersion and trajectory behavior was determined by the use of Krypton-85 as a tracer gas. The results reinforce the conclusion advanced in the previous study that Pasquill-Gifford prediction methods apply well to the site. The shelterbelt study consisted of evaluating the effects of porosity, barrier height and length, geometric configuration of barriers, parking lot orientation and wind approach angle upon the protection of parking areas from high velocity wind action in assaulting vehicles with abrasive particles. Tests were accomplished by observing the effectiveness of the wind in transporting a zinc oxide-mineral oil suspension. This effectiveness was correlated to velocity reduction and wind profile modification effectiveness of shelterbelts. It was found that the most effective use of shelterbelts could be accomplished if the parking lot were reoriented with the long side running in a north-south direction.
Prepared for Research and Ecology, Rocky Flats Division, Dow Chemical Company.
CER72-73RNM-JAP-TGH-16.
March 1973.
Keywords: Dow Chemical Company. Rocky Flats Division; Wind tunnel models